2012
DOI: 10.1016/j.neurobiolaging.2010.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Impact of changed positive and negative task-related brain activity on word-retrieval in aging

Abstract: Previous functional imaging studies that compared activity patterns in older and younger adults during non-linguistic tasks found evidence for two phenomena: older participants usually show more pronounced task-related positive activity in the brain hemisphere that is not dominant for the task and less pronounced negative task-related activity in temporo-parietal and midline brain regions. The combined effects of these phenomena and the impact on word-retrieval, however, have not yet been assessed. We used fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
88
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(99 citation statements)
references
References 60 publications
10
88
0
1
Order By: Relevance
“…As in previous studies that used similar word generation designs (Meinzer et al, 2009(Meinzer et al, , 2012) a whole-brain comparison of correct semantic word generation trials with the baseline condition (saying the word "rest" aloud) elicited a reliable and highly consistent pattern of task-related activity for both conditions. Most pronounced activity was found in the lateral (ventral and dorsal) IFG and medial frontal areas, but also left posterior temporal and parietal areas and the right inferior frontal gyrus [ Fig.…”
Section: Fmri Revealed Specific Task-related Activity Reductions Durisupporting
confidence: 69%
See 3 more Smart Citations
“…As in previous studies that used similar word generation designs (Meinzer et al, 2009(Meinzer et al, , 2012) a whole-brain comparison of correct semantic word generation trials with the baseline condition (saying the word "rest" aloud) elicited a reliable and highly consistent pattern of task-related activity for both conditions. Most pronounced activity was found in the lateral (ventral and dorsal) IFG and medial frontal areas, but also left posterior temporal and parietal areas and the right inferior frontal gyrus [ Fig.…”
Section: Fmri Revealed Specific Task-related Activity Reductions Durisupporting
confidence: 69%
“…In the language domain, increasing proficiency in a newly learned second language is associated with more focal left-lateralized activity in prefrontal cortices, resembling the network active during language processing in the mother tongue (Abutalebi, 2008). Furthermore, increased bilateral IFG activity is associated with reduced semantic word-generation performance in healthy aging (Meinzer et al, 2009(Meinzer et al, , 2012, and even in young adults when task demands are increased (Thompson-Schill et al, 1997). Other studies found increased activity after tDCS.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Age-related neural differences for semantic versus phonemic fluency were also identified in a study by Meinzer et al (2012). The findings showed increased right IFG by the older adults accompanied by a reduction in behavioural performance in semantic fluency, suggesting that semantic and phonological processing may differ as a function of age.…”
Section: Neural Correlates Of Concrete and Abstract Processing In Heamentioning
confidence: 63%